Analisis Proses Bisnis Berbasis Data melalui Implementasi Dashboard - Andi Nuralvianti; Muhammad Jamil; Valentino Aris (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to implement a data dashboard as a decision-support tool for analyzing business processes at KPRI Mart. The research addressed two main objectives: to design a data dashboard that aligns with business analysis needs and to evaluate its effectiveness in supporting managerial decision-making. The implementation of a digital dashboard represents an essential step toward enhancing data-driven decision-making and improving operational efficiency within modern retail cooperatives. Materials and methods. This study employed a Research and Development (R&D) approach and adopted the Software Development Life Cycle (SDLC) model as the framework for system development. The dashboard was developed using Microsoft Power BI, chosen for its ability to integrate multi-source data and provide interactive visualizations. The dataset used consisted of three years of historical sales data (2022–2024) from KPRI Mart. Functional validation was conducted through the Black Box Testing method to ensure that all interactive features and visualization components performed according to the design specifications. Results. The developed dashboard successfully visualized key business metrics, including monthly sales trends, total units sold, and total sales values. These visualizations enabled store coordinators to interpret business performance more efficiently and respond to sales dynamics more strategically. The Black Box Testing results confirmed that all dashboard functions operated properly and aligned with user requirements. Conclusions. The findings indicate that the implemented dashboard enhances business process analysis by providing real-time, accurate, and informative data visualizations. This contributes to more efficient and data-driven managerial decision-making. The study highlights the importance of digital transformation through Business Intelligence tools to help cooperative organizations remain adaptive and competitive in a continuously evolving economic environment.